(untitled) (Tempo e Argumento, 2011)
This article presents an ongoing research, supported by CNPq (Conselho Nacional de Desenvolvimento Científico e Tecnológico) and by the Pró-reitoria de Pesquisa of the Universidade de São Paulo, about the interactions between the expressions of the promise keepers of the Círio of Nazareth at Belém of Pará, the “Warriors” players of the Alagoan Christmas-auto and the universe of architectural scale models, understood as objects with small size and architectural shape. This study deals, more precisely, with the interactions of those expressions with the "artistic motif of the architectural model holder", a typical medieval figuration that features a character holding a small size object with architectural forms, as a scale model. Over these urban cultural goods, the proposed approach is based on the notion of "survival", "nachleben" or “survivance”, on the understanding of long-term phenomena deeply rooted in the collective memory, and also on the concept of "pathosformeln". In methodological terms this research proposes a visual and anthropological approach to the mentioned phenomena, contextualizing and articulating them to imaginary universe of architectural representations.